Efektivitas Pembiasaan Belajar Mengaji Dalam Mengembangkan Nilai Agama dan Moral Pada Anak Usia Dini (AUD) Di Desa Sempa Jaya, Kabupaten Karo - Wahyuni, Sri; Hasibuan, Nurul Fadhila; Fadhila, Luthfita Rizka; Syahrin, Nur Hasana Alvi; Hasanah, Nurul Afni; Hasri, Putri Puspita (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effectiveness of habitual Quranic recitation (mengaji) in developing religious and moral values in early childhood (AUD) in Sempa Jaya Village, Karo Regency. Quranic recitation is a crucial part of religious education in the village's Muslim community, with strong support from parents and community leaders. This research employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that regular Quranic recitation activities successfully enhance children's understanding of religious teachings, particularly in worship and ethics. The children also exhibit moral value development, such as empathy, responsibility, and cooperation. The main supporting factor for the success of this habitual practice is family support, while challenges include the limited availability of religious education facilities and competent teachers. The conclusion of this study reveals that habitual Quranic recitation positively impacts the development of religious and moral values in AUD, though improvement in facilities and teacher training is needed.